Is Co-production Just a Pipe Dream for Applied Health Research Commissioning? An Exploratory Literature Review - Tembo, Doreen; Morrow, Elizabeth; Worswick, Louise; Lennard, Debby (Frontiers in Sociology, 2019)
Background and Rationale: Internationally, the idea of ‘co-production’ has become more popular in health research because of the promise of partnership between researchers and patients to create research that focuses on patient’s needs. Patient and public involvement (PPI) at an early stage in deciding what research should be funded, can improve the quality and impact of research. However, professional power over the process places limits on the public practicing their participatory rights for involvement in commissioning research that affects them and can leave members of the public feeling unheard or excluded, particularly within the context of early phase applied health research. Aim: This article explores whether and how the public can be involved in the co-production of research commissioning early on in the process, with a focus on the power relations that pervade basic and early phase translational applied health research. Methods: An exploratory literature review of international peer-reviewed and grey health research literature using structured searches of electronic databases and key search terms. Results: There is very little literature that critically evaluates how PPI is embedded into the early phases of the commissioning process. The field of basic or early translational applied research appear to be particularly challenging. Four themes which emerged from the review are: reasons for PPI in research commissioning; benefits of PPI at strategic levels of research commissioning; contributions of patients and members of the public; improving PPI in research commissioning. Conclusion: Although the public are being consulted at some stages of the research commissioning process, it is evident that the process of determining research priorities and agendas is far from being widely co-produced. Moving PPI from a consultative paternalistic model to a collaborative partnership model should be a priority for commissioners. Significant changes to communication, practices, systems, structures or cultures that exclude patients and the public from contributing in meaningful ways, are needed to fulfil the potential of co-produced models of research commissioning.